Simultaneous Recording and Analysis of Uterine and Abdominal Muscle Electromyographic Activity in Nulliparous Women During Labor. (March 2017) - Qian, Xueya; Li, Pin; Shi, Shao-Qing; Garfield, Robert E.; Liu, Huishu
Objective: To record and characterize electromyography (EMG) from the uterus and abdominal muscles during the nonlabor to first and second stages of labor and to define relationships to contractions. Methods: Nulliparous patients without any treatments were used (n = 12 nonlabor stage, 48 during first stage and 33 during second stage). Electromyography of both uterine and abdominal muscles was simultaneously recorded from electrodes placed on patients' abdominal surface using filters to separate uterine and abdominal EMG. Contractions of muscles were also recorded using tocodynamometry. Electromyography was characterized by analysis of various parameters. Results: During the first stage of labor, when abdominal EMG is absent, uterine EMG bursts temporally correspond to contractions. In the second stage, uterine EMG bursts usually occur at same frequency as groups of abdominal bursts and precede abdominal bursts, whereas abdominal EMG bursts correspond to contractions and are accompanied by feelings of "urge to push." Uterine EMG increases progressively from nonlabor to second stage of labor. Conclusions: (1) Uterine EMG activity can be separated from abdominal EMG events by filtering. (2) Uterine EMG gradually evolves from the antepartum stage to the first and second stages of labor. (3) Uterine and abdominal EMG reflect electrical activity of the muscles during labor and are valuable to assess uterine and abdominal muscle events that control labor. (4) During the first stage of labor uterine, EMG is responsible for contractions, and during the second stage, both uterine and abdominal muscle participate in labor.